The Effect of Competence and Knowledge Management on Employee Performance (Case Study At The Indonesian University Of Education, Tasikmalaya Campus) - Herdiyana, Peri; Budianto, Apri; Herman, Ferey; Aljamaliah, S. Nailul Muna (A Social Science and Entrepreneurship Journal, 2023)
The research was conducted to know the effect Competence and Knowledge Management on Employee Performance At the Indonesian University of Education, Tasikmalaya Campus. The method used is a quantitative descriptive method. The research results show that Competence positively and significantly affects the performance of Administrative Section Employees of the UPI Tasikmalaya Campus. This means that if the competence of employees increases, the performance of the Administrative Section Employees will also increase. Knowledge management positively and significantly affects the performance of Administrative Section Employees of the UPI Tasikmalaya Campus. This means that if knowledge management increases, the performance of Administrative Officers will also increase. Competence and knowledge management have a positive and significant effect on the performance of Administrative Section Employees of the UPI Tasikmalaya Campus. This means that if competence and knowledge management increase, the performance of the Administrative Section Employees also increases.